Dreaming of motherhood: experiences of women who have undergone fertility treatment - Rujas Bracamonte, Sara; Serrano Gallardo, Pilar; Martínez Marcos, Mercedes (Investigación y Educación en Enfermería, 2025)
Objective. to describe the strategies used by women who have undergone assisted reproductive technologies (ART) to cope with the process of becoming mothers and to describe their relationships with their partners and healthcare professionals throughout this process. Methods. This is a qualitative study based on grounded theory. Twenty women who had undergone ART in Spain were selected. Semi-structured interviews were used to collect the data. The analysis followed grounded theory methods. Results. ‘Fighting for a dream: motherhood’ is the main category describing women’s struggles from their diagnosis of infertility to their successful pregnancy and delivery. This process makes it possible for them to fulfil their dream and become parents along with their partners. Three subcategories describe the different stages in the process: ‘Accepting treatment: doing everything possible’, ‘Undergoing treatment: an emotional rollercoaster’, and ‘Reconsidering the dream: give up or gather strength to keep going?’ Conclusion. Women undergoing ART experience difficulties as they seek to achieve pregnancy, as there is no guarantee that they will be able to fulfil their greatest desire in life: motherhood. Women use a variety of coping strategies during ART and continue to seek emotional support from their peers and/or women who are experiencing the same situation.